The method of multi-criteria comparative analysis of management Staff competency assessment systems - Tyrańska, Małgorzata (Metody i techniki zarządzania. Inspiracje dla teorii i praktyki, 2020)
The purpose of the chapter is to present an example of applying an idea of multi-criteria comparative analysis in the evaluation practice of management staff competency assessment systems. The chapter depicts the assumptions of multi-criteria comparative analysis of management staff competency assessment systems and the implementation stages of the proposed methodology. The presented evaluation approach to the management staff competency assessment systems, that is carried out using a greater number of criteria, gives the opportunity to compare many of the analyzed systems with each other in order to identify the best and the weakest solutions for assessing the management staff competencies and to set directions for their improvement.